Angelus Silesius: Some Lesefrüchte on the Background to Lacan’s Seminar - John Gale (EJP import test, 2020)
[caption id="attachment_2579" align="alignleft" width="671"] "Rods" by Stephen Mosblech[/caption] Summary: This paper gives the wider background to the references in Lacan’s work to the life of Angelus Silesius, the pseudonym of Johann Scheffler [1624-1677], and his principle mystical text, the Cherubinische Wandersmann. A text almost certainly written between 1651 and 1653, a period of deeply personal transition and transformation which culminated in his reception into the Catholic Church and his decision to become a Jesuit. It includes a summary of the development of Christian mysticism in the West and the immediate context in which Lacan’s interest in the mystical emerged. This latter included a study of Silesius by Jean Baruzi. While Derrida and others have considered Silesius’ work not truly mystical, this paper argues that this is to over subscribe to a view in which the mystical is reduced to subjective, individual experience. A reading that only became common in the eighteenth and nineteenth centuries.
Keywords: Angelus Silesius; apophatic; Lacan; mystic; mysticism; The mysteries